Index - Publicación TELOS (Telos: Revista de Estudios Interdisciplinarios en Ciencias Sociales, 2004)
The plot of research and its epistemology The Problems of Research and its Epistemology Hermelinda Camacho, Tomas Fontaines Ruiz and Geovanni Urdaneta